Characteristics of early sacubitril/valsartan patients and considerations for studies in electronic health record data. (29th August 2018) - Gagne, Joshua J; Tsacogianis, Theodore; Bruce Wirta, Sara; Rogers, James R; Calado, Frederico; Chang, Chun-Lan; Turner, Stuart J; Schlienger, Raymond G; Balas, Bogdan; Abdurrob, Abdurrahman; Najafzadeh, Mehdi; Wang, Shirley V
Aim: We examined characteristics of early sacubitril/valsartan users in a large US electronic health records database.Patients & methods: We identified three cohorts of patients with heart failure (HF): sacubitril/valsartan patients with a prior HF diagnosis; patients with HF with reduced ejection fraction; and patients with HF treated with an angiotensin-converting enzyme inhibitor or angiotensin II receptor blocker and a β-blocker.Results: Sacubitril/valsartan patients were younger than patients in the other cohorts; the mean age of sacubitril/valsartan patients increased by 2 years in the first 15 months of marketing. Most sacubitril/valsartan patients had prior use of HF treatment.Conclusion: Overall, sacubitril/valsartan patients resembled those in the HF with reduced ejection fraction cohort, and commonly used other drugs for HF.